2014
DOI: 10.1039/c4cc03649b
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of gallium in the presence of NH4Cl in an ionic liquid: hints for GaN formation

Abstract: Group III-V semiconductors are important in the production of a variety of optoelectronic devices. At present, these semiconductors are synthesized by high vacuum techniques. Here we report on the electrochemical deposition of GaN which seems to form in quite a thin layer from NH4Cl and GaCl3 in an ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…CV was stopped at the initial open‐circuit potential to avoid oxidation of the copper electrode. The CV results are consistent with previously reported data 24. Figure 1 b shows the CV results for 0.1 M GeCl 4 in [Py 1,4 ]Tf 2 N on electrodeposited gallium.…”
Section: Resultssupporting
confidence: 92%
“…CV was stopped at the initial open‐circuit potential to avoid oxidation of the copper electrode. The CV results are consistent with previously reported data 24. Figure 1 b shows the CV results for 0.1 M GeCl 4 in [Py 1,4 ]Tf 2 N on electrodeposited gallium.…”
Section: Resultssupporting
confidence: 92%
“…Recently, it has been demonstrated that instead of lattice matched substrates, surfaces with appropriate buffer layers could also be used for growing high-quality GaN films. [8][9][10] Certain soft chemical methods [11][12][13][14][15][16][17][18][19][20][21][22][23] have also been proposed but the preparation of high-quality GaN films via a chemical route is still a challenge. There have been reports on the synthesis of GaN powders 13,14 and GaN nanocrystals from different gallium precursors.…”
mentioning
confidence: 99%
“…The IR and Raman spectra of 2 b clearly show the absence of the [NO] + stretching frequency of the starting material, indicating a complete reaction (see the Supporting Information). The observation of the symmetric breathing mode of [GaCl 4 ] − at trueν˜ =339 cm −1 in the Raman spectrum proves that it is more comparable with weakly coordinated salts like [NH 4 ] + [GaCl 4 ] − (trueν˜ =342 cm −1 ) . More coordinating cations induce blueshifts, like in Li + [GaCl 4 ] − (trueν˜ =348 cm −1 ) or the starting material [NO] + [GaCl 4 ] − (trueν˜ =350 cm −1 ).…”
Section: Resultsmentioning
confidence: 83%
“…The observation of the symmetric breathing mode of [GaCl 4 ] À at ñ = 339 cm À1 in the Raman spectrum provest hat it is more comparable with weakly coordinated salts like [NH 4 ] + [GaCl 4 ] À (ñ = 342 cm À1 ). [51] More coordinating cations induce blueshifts, like in Li + [GaCl 4 ] À (ñ = 348 cm À1 )o rt he starting material[NO] + [GaCl 4 ] À (ñ = 350 cm À1 ).…”
Section: Synthesis Of Gold(i) Salts Of Weakly Coordinating Anionsmentioning
confidence: 99%